Penerapan Green Accounting di Polrestabes Palembang - Nadila Nadila; Septiani Fransisca (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This study aimed to evaluate the implementation of green accounting at Polrestabes Palembang and its impact on sustainable environmental management. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation for data collection. The findings revealed that green accounting practices at Polrestabes Palembang were not yet fully integrated into the institution’s financial accounting system. Environmental costs were still recorded under general operational expenses without specific classifications, and there was no systematic measurement or disclosure in accordance with environmental accounting principles. However, several positive initiatives existed, such as energy efficiency, greening efforts, waste management, and food security programs. The study recommends strengthening environmental cost recording systems, integrating data across departments, and providing training to enhance understanding of green accounting. Effective implementation of green accounting is expected to improve transparency, accountability, and institutional legitimacy in supporting sustainable development.